Answer:
is an expression which describe the given sequence
Step-by-step explanation:
Arithmetic sequence states that a sequence where the difference between each successive pair of terms is the same.
The general rule for the arithmetic sequence is given by;
......[1]
where
represents the first term
d represents the common difference
and n is the number of terms;
Given sequence: -1 , 0 , 1 , 2 , .....
This is an arithmetic sequence with common difference
Since,
0-(-1) = 1
1-0 =1
2-1 = 1 ....
Here, ![a_1 = -1](https://tex.z-dn.net/?f=a_1%20%3D%20-1)
Substitute the value of
, d =1 in [1] we get
![a_n = -1 + n -1 = -2 +n](https://tex.z-dn.net/?f=a_n%20%3D%20-1%20%2B%20n%20-1%20%3D%20-2%20%2Bn)
Therefore,an expression which describe the given sequence is, ![a_n = -2 + n](https://tex.z-dn.net/?f=a_n%20%3D%20-2%20%2B%20n)